Computational study of a toxin neutralization by antibody in the well-mixed solution - Katauskis, Pranas; Dzimidaitė, Justina (Lietuvos matematikos rinkinys, 2013)
A mathematical model decribing the interaction of toxin, antibody and cell receptors when cell is placed in the well-mixed solution of toxin, antibody and toxin–antibody complex is studied. The protective properties of an antibody against toxin are investigated numerically choosing the model parameters.
Keywords: toxin; antibody; receptor; cell protection